Optimization of chicken eggshell as pore forming agent in porous ceramic using response surface methodology (RSM) statistical design - Muhammad Aiman Azim Abd Aziz (2024)
Ceramics that are porous have a high porosity percentage, which can range from 20% to 95%. In many different applications, such filtering systems, thermal insulators, and biomedical, porous ceramic is essential. Pore-forming agent (PFA) and ceramic powder make up a porous ceramic composition. Researchers looked into the viability of using food waste (coffee grounds and banana peels) as PFA to make porous porcelain. The food waste's high moisture content makes the waste preparation process challenging. It was discovered that chicken eggshells had a lower moisture content than other food waste, which will make the waste preparation process practical. The objective of this study to produce and characterize porous ceramic that incorporated chicken eggshell as a pore-forming agent (PFA). Using Response Surface Methodology (RSM) statistical approaches to optimize the weight percentage of added chicken eggshell and the sintering temperature to the physical and mechanical properties of the porous ceramic. Porous network ceramic structures are generally light and possess low mass, low density, and poor heat conductivity. Porous ceramic is created by combining pore-forming agents (PFA) with ceramic powder. A water absorption test, apparent porosity, bulk density, and crystalline phase (XRD characterization) were used to determine the physical properties. The mechanical properties were determined by compressive strength. The results showed that increasing the weight % of chicken eggshell (CES) in the porous ceramic reduces compressive strength and increases porosity. The purpose of this study is to determine the optimal optimization for porous ceramics by analyzing data from Minitab 16 using Response Surface Methodology (RSM) Statistical Design.